The relative importance of Integrated Marketing Communications (IMC) components in the fuel industry in South Africa - Stuart, Donald Malcom (My University, 2011)
Marketers in the fuel retail industry in South Africa communicate with customers and prospects through advertising, sales promotions, the sales force, publicity and sponsorship and point of purchase communications. These instruments of communication have very specific functions. They are generally used discretely to achieve the objective of each instrument. The relative importance of each component regarding effectiveness and contribution to sales is not known. Integration of the components of marketing communications is at an early stage. The objective of this study was to determine the relative importance of integrated marketing communications (IMC) components in the fuel retail industry in South Africa. To investigate the relative importance of the IMC components, fifteen in-depth interviews were conducted with managers and owners of established and emerging fuel brands in the fuel retail industry. The main findings of this research were; that advertising was the most important component of IMC, followed by sales promotion, which was more important than sales force abilities in the retail fuel industry. The research effort could not distinguish the relative importance between point-of-purchase communications and public relations and sponsorship. It was established that integration of the components of IMC based on relative importance improved effectiveness of communications components and created the opportunity for interaction with the market. Integration on the basis of relative importance contributed to elevating the communication from a tactical effort to a strategic initiative. Using the components for communication, whilst being cognisant of the relative importance, supports the strategy and allocating the marketing budget, according to relative importance, improves sales
MBA - WBS
Keywords: Petroleum fuel industry; Marketing communications; Communications, Marketing